2015
DOI: 10.1016/j.ibusrev.2015.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Does country context distance determine subsidiary decision-making autonomy? Theory and evidence from European transition economies

Abstract: We studied an underrepresented area in the international business (IB) literature: the effect of country context distance on the distribution of decision-making autonomy across headquarters and foreign affiliates. Foreign affiliates directly contribute to the competitive advantages of multinational enterprises, highlighting the importance of such intra-firm collaboration. The division of decision-making autonomy is a core issue in the management of headquarterssubsidiary relationships. The main contribution of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 107 publications
(139 reference statements)
3
45
0
Order By: Relevance
“…The global city location seems to play only a peripheral role overall and only the absence of geographical distance is relevant in a number of solutions. This seems to indicate that locational factors seem to play a less conducive role than often suggested (e.g., de Jong et al, ; Goerzen et al, ; Mudambi, ). For instance, the global city location is only a substitute for the absence of the other conditions in a relatively small number of cases as seen in solutions 7 of the autonomy in basic value‐adding activities and solution 6 in the high value‐adding activities.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…The global city location seems to play only a peripheral role overall and only the absence of geographical distance is relevant in a number of solutions. This seems to indicate that locational factors seem to play a less conducive role than often suggested (e.g., de Jong et al, ; Goerzen et al, ; Mudambi, ). For instance, the global city location is only a substitute for the absence of the other conditions in a relatively small number of cases as seen in solutions 7 of the autonomy in basic value‐adding activities and solution 6 in the high value‐adding activities.…”
Section: Discussionmentioning
confidence: 69%
“…Space refers to the geographic distance between home and host country of the MNE. For instance, previous studies have shown with increasing geographic distance, the familiarity of the MNE decreases; hence, information costs increase as well as liability of foreignness (Alcácer et al, ; de Jong et al, ). Place refers in this study to global cities.…”
Section: Literature Review and Research Questionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Having still many value chain activities carried out at home, increases the likelihood to keep marketing planning and control at headquarters. The choice also demonstrates companies' general tendency to consider marketing activities as a low-autonomy function (De Jong, van Dut, Jindra, & Marek, 2015). It seems that this is linked to automotive companies' willingness to maintain a strong coherence of all their marketing activities.…”
Section: Discussionmentioning
confidence: 90%